THE IMPORTANCE OF CBCT EXAM IN DIAGOSIS AND TREATMENT OF DENTINGEROUS CYSTS AT THE CHILD - Ana Petcu (Sîrghe); Cristian Romanec; Carmen Savin; Aris Prisacariu-Rados; Bogdan Dragomir (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study was to evaluate the advantages of radiological exam, especially of CBCT, in diagnose and treatment planning of dentigerous cyst in children and adolescents. Material and methods The study included a total of 163 CBCT exams. The radiation dose absorbed was also influenced by the irradiated area and its magnitude, the intensity and voltage of the tube current as well as the exposure time. Results The most common indication for CBCT exam is the location of the included teeth, mainly in the included canines. Bone pathologies recorded 23 investigations, including 21 cysts, 2 odontoma. From these 21 cysts, it was found 15 dentigerous cyst and 6 odontogenic keratocyst. Conclusions CBCT is used for treatment planning of dentigerous cysts because it provides the most detailed information about surround anatomical structures and relations among them.